GERAKAN SISWA MENGAJAR (GSM) IMPLEMENTASI METODE TUTOR SEBAYA DI SMPN 1 MEJAYAN KABUPATEN MADIUN - Mustofa Aji Prayitno (Fakultas Tarbiyah Institut Agama Islam Ngawi, 2021)
This study aims to determine the stages of implementing the peer tutoring method in the learning process and the implementation of the Teaching Student Movement (GSM) at SMP Negeri 1 Mejayan, Madiun Regency. Data collection techniques used in this study using triangulation techniques. Analysis of research data was carried out in three stages, namely the stage of data reduction, data presentation, and drawing conclusions. The results showed that: (1) The stages of implementing the peer tutoring method in the GSM (teaching student movement) program at SMP Negeri 1 Mejayan Madiun Regency included three stages, namely the preparation stage, the implementation stage, and the evaluation stage. (2) In its implementation, the GSM (teaching student movement) program at SMP Negeri 1 Mejayan applies a creative, innovative and fun system, the aim is to optimize the active role of students in the learning process, as an effort to increase student test scores, especially in the graduation exam and national exam ( UN), optimizing academic potential and character values ​​in students, as well as realizing a creative, innovative, and fun learning process. Key Words: Student Teaching Movement, Peer Tutor, SMPN 1Mejayan